Infectious Eye Diseases - Recent Advances in Diagnosis and Treatment 2021
DOI: 10.5772/intechopen.96752
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Toxoplasmosis: An Update on Diagnosis, Multimodal Imaging and Therapy

Abstract: Ocular toxoplasmosis remains to be the most common cause of infectious uveitis in immunocompetent individuals with highly variable prognosis. The transmission mode can be either congenital or acquired. A precise diagnosis of the disease is necessary to opt effective and rapid treatment. While ocular toxoplasmosis usually presents in the classic form, it may as well present in variable clinical spectrum. The diagnosis can be suspected by the ocular inflammatory clinical presentation as well as multimodal imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 97 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Toxoplasma neuroretinitis should be distinguished from idiopathic neuroretinitis as idiopathic neuroretinitis is self-limited while the former requires timely treatment for resolution [2]. Although there is a lack of randomized control studies for treatment of toxoplasma neuroretinitis, it is suggested that oral antibiotics and corticosteroids may prevent permanent damage to the optic nerve [1,2,4,[6][7][8][9].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxoplasma neuroretinitis should be distinguished from idiopathic neuroretinitis as idiopathic neuroretinitis is self-limited while the former requires timely treatment for resolution [2]. Although there is a lack of randomized control studies for treatment of toxoplasma neuroretinitis, it is suggested that oral antibiotics and corticosteroids may prevent permanent damage to the optic nerve [1,2,4,[6][7][8][9].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The patient did not initially show prompt clinical improvement despite being on the empiric regimen and was therefore provided with intravitreal clindamycin. Intravitreal injection of clindamycin is well-tolerated with high bioavailability, avoids systemic side effects, and can be given for persistent cases [8,9]. This additive treatment resulted in a positive outcome with a complete resolution of ocular pathology and return of vision.…”
Section: Discussion/conclusionmentioning
confidence: 99%